A Bayesian spatial econometric analysis of the 2010 UK General Election. (7th February 2012) - Jensen, Christa D.; Lacombe, Donald J.; McIntyre, Stuart G.
Abstract: The Conservative Party won the 2010 General Election in the United Kingdom, gaining the most votes and seats of any single party. Using Bayesian spatial econometric methods, we show that significant spatial dependence exists in Conservative voting behaviour and select the spatial Durbin model as the best model to explain this phenomenon. This paper examines these spatial effects as well as the effects of a range of economic, socio‐economic, and political variables. Perhaps the most interesting result is that incumbency has effects beyond an incumbent's own constituency.